Cambio de uso y rediseño interiorista del Teatro Álvarez para la Casa de la Juventud sede Espejo – Carchi - Vallejo Carrera, Marcelo Cristobulo (2018)
The project is about the change of use of the Álvarez Theater located in the city of El Ángel, to turn it into the House of Youth, Espejo - Carchi. This building keeps many memories and affection by the citizens, because it was the only place of social gathering for many decades throughout the city. On the other hand, the House of Youth is an entity that has been responsible for the cultural and intellectual development of children and adolescents in the province of Carchi. The proposal is to a potential user that goes from 5 to 18 years old, being guided in Art, Leadership, Theater, Dance and Music. The change of use consists of the preservation of the rampart that forms the theater and inserts a new structure that respects the old one, and works by itself. Respecting the existing and creating a contrast with the new proposal. The box of games was taken as a concept, achieving an organized composition of geometric figures that shape the interior spaces, which in turn is crossed by a diagonal axis of circulation. Interactive vertical circulation mechanisms are proposed through slides, which give dynamism to the space and serve to integrate and invite people of different ages.